Pemberian Dedak Padi yang Difermentasi dengan Bacillus amyloliquefaciens sebagai Pengganti Ransum Komersil Ayam Ras Petelur - Wizna Wizna; H Muis (Universitas Andalas, 2012)
This experiment was carried out to study the effect of substitution of TSI ration with rice bran fermented with Bacillus amyloliquefaciens on feed comsumtion, henday production, egg mass and feed convertion of layer. This experiment was designed using a Completely Randomized Design (CRD) with six treatments. Each treatment three replicates at twelve layer each. The treatment were diets which contained substitution of 20% (A), 30% (B), 40% (C), 50 % (D), 60% (E) and 70% TSI with rice bran fermented with Bacillus amyloliquefaciens (F), resvectively. Feed and water was offered ad libitum. Result of this experiment showed that feed comsumtion, henday production, egg mass and feed convertion were highly affected (P<0.01) by treatment but not affected to henday production. It was concluded that substitution of 40% TSI ration with rice bran fermented with Bacillus amyloliquefaciens was decreased feed comsumtion and feed convertion of layer.